Mechanism and Predictive Role of NUB1 Protein in Oestrogen Receptor Pathway of FEC-Treated Breast Cancer Patients - Maria Arshad; Amira Raudhah Abdullah; Fuad Ismail; Francesco Pezzella; Azyani Yahaya; Geok-Chin Tan; Suet Lin Chia; Md Salzihan Md Salleh; Noraidatulakma Abdullah; Ka-Liong Tan (MDPI, 2026)
Tier 1- Indexed by WOS